Design and Strength Analysis of Ladder Models Frame with AISI 1015 1018 1020 Steel: Desain dan Analisis Kekuatan Ladder Frame dengan Bahan Baja AISI 1015 1018 1020 - Wahyudi, Irfan Sholeh; Kosjoko; Mufarida, Nely Ana (R.E.M. (Rekayasa Energi Manufaktur) Jurnal, 2024)
Sport Utility Vehicle Chassis Design. This design/research is about the design and analysis of Sport Utility Vehicles. A car's vehicle frame is the most important component of a car's transportation system. This chassis is designed to withstand the load borne by passengers and other loads. Because they are so heavy, the rigidity of the frame and the materials used to make it must be taken into account during the process of making components suitable for the load. Because the Ladder Frame chassis is known to be strong. The materials used are AISI 1015, AISI 1018 and AISI 1020 steel for validation of calculations. The results show that the stress value is 0.00002013 mm. Strain 0.000008446 mm. Placement 0.007189 mm. and the chassis safety factor is at a safe value of 0.00000004657 mm, with a load of 650 Kg. The results obtained were that the center of mass of the chassis was more rigid with AISI 108 Steel based on Solidworks software. Then the chassis is more resilient and strong and it can be concluded that this design is safe, feasible and meets the criteria for the materials used.